FLUKTUASI TEMPORAL KELEMBABAN UDARA DI DALAM DAN LUAR EKOSISTEM MANGROVE - Dalengkade, Mario Nikolaus (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2020)
Modeling air humidity in the mangrove ecosystem using Fourier functions shows a cycle of temporal fluctuations. The cycle is influenced by the intensity of the sun. Graphical modeling of air humidity shows similarities for position 1 and position 3. Starting at 19.00 air humidity is 72% and continues to rise reaching 85.5% at exactly 04.00. Then it declined again by 59.2% at 12.00. Unlike the 9th position starting at 19.00 the value of air humidity is 71.5% and continues to rise reaching 82.5% at exactly 4:00 a.m., and decreases again to reach 65% at 12.00. The difference in the value of air humidity is because position 1 and position 3 are located outside and the edge of the mangrove forest where no or lack of mangrove canopy cover causes the evaporation process to occur very quickly. While position 9 is located in the mangrove forest where the mangrove canopy cover plays an important role in controlling the evaporation process and reducing the intensity of the sun. Besides that cross-choreal testing produces a time‒lag that varies for each position measuring air humidity based on the depth and edge of the mangrove ecosystem.